DRIS norms and limiting nutrients in banana cultivation in the South of Ecuador - Villaseñor, Diego [UNESP]; Prado, Renato de Mello [UNESP]; Pereira da Silva, Gilmara; Carrillo, Manuel; Durango, Wuellins (Taylor & Francis, 2020)
Foliar analysis is an effective method to diagnose the nutritional status of plants. However, the mineral concentration in foliar tissue has traditionally been evaluated by assessing the activity of each element, without considering the interactions between them. To address this, dual interactions were calculated using the Diagnosis and Recommendation Integrated System (DRIS) to identify which crop nutrients are most influential in nutrient imbalances and which are the most limiting nutrients for the nutritional status of banana crops in Ecuador. To achieve this, a regional survey of the nutritional status and its productivity levels was conducted for 188 different sites during the crop season in 2017–2018, involving banana cultivars ‘Vallery’ and ‘Williams’, from the Cavendish subgroup. The DRIS calculation method was combined with Beaufils and Jones functions. From the initial 188 foliar samples, 83 samples (representing 44% of the population) were considered to represent the high-yield reference population, with yields of 38–60 t ha−1. The DRIS method defined the mean nutritional balance index, which was not found to be statistically correlated (p > 0.05) with productivity, revealing that there was no significant association with the nutritional status of the plants. Specific DRIS norms were obtained and indicated that deficiencies in K, N, Ca, and Fe, and excesses in Mn, B, Cl, Zn, S, Cu, and Mg were the most limiting nutrients for banana cultivars in the south of Ecuador.
Keywords: diagnostic indices; leaf analysis; leaf standards; Musaspp; nutritional balance; plant nutrients